An Analysis on the Implementation of the Evidence-based PCOS Lifestyle Guideline: Recommendations from Women with PCOS - Lim, Siew; Wright, Breanna; Savaglio, Melissa; Goodwin, Denise; Pirotta, Stephanie; Moran, Lisa (Seminars in Reproductive Medicine, 2021)
Polycystic ovary syndrome (PCOS) is the most common endocrinological disorder affecting women of reproductive age, affecting 8–13% in this group. Women with PCOS are more likely to have excess BMI, which in turn exacerbates the symptoms of PCOS in these women. The latest evidence-based guideline recommends lifestyle management as the first-line treatment for PCOS. However, the implementation of this recommendation through health services faces a significant challenge. As part of the mapping of the implementation plan for lifestyle management in PCOS, citizen panels and semi-structured interviews were conducted to capture the voices of consumers. Women with PCOS expressed the need for multidisciplinary, integrated care as a recurrent theme. Other important considerations included health professionals who listen and are open to learning about PCOS, the empowerment of women to self-manage PCOS and the provision of peer support. Women with PCOS also expressed the key recommendation of focusing on practical skills when providing lifestyle advice. Within that, both individual and group lifestyle sessions were valued for privacy and peer support respectively and delivery by a dietitian is preferred. These recommendations by women with PCOS should be considered when developing the implementation plan for the PCOS lifestyle guideline.
Keywords: polycystic; women; lifestyle; guidelines; implementation